2020
DOI: 10.29121/granthaalayah.v8.i4.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Resilience: a Challenge of Commitment and Effectiveness

Abstract: Teaching is an emotionally demanding work.  To teach, and to teach at one’s best over time, has always required resilience, otherwise conflict within the self and classroom routine will set in.  Anchored on the theories of resilience, motivation, self-determination, personal values, and capability approach, this case study will describe on the consequences of teachers’ resilience on its commitment and effectiveness to teaching.  Eight teachers of the Department of Education assigned in island schools in Guiuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Polat and Iskender (2018) conducted a study that was descriptive in nature and found that TR, work satisfaction, fatigue, business commitment, and an evaluation of the organizational environment are closely linked. The research carried out by Lacaba et al (2020) proved the implications that teachers' levels of resilience have on their levels of devotion and effectiveness. The teachers were aware of the present issues in their teaching practice; yet, they needed to develop their resilience in order to boost their effective teaching and demonstrate their work participation, as demonstrated by the results (Fig.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Polat and Iskender (2018) conducted a study that was descriptive in nature and found that TR, work satisfaction, fatigue, business commitment, and an evaluation of the organizational environment are closely linked. The research carried out by Lacaba et al (2020) proved the implications that teachers' levels of resilience have on their levels of devotion and effectiveness. The teachers were aware of the present issues in their teaching practice; yet, they needed to develop their resilience in order to boost their effective teaching and demonstrate their work participation, as demonstrated by the results (Fig.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Luna, it is of critical importance to correlate these findings in the view of Gu and Day (2013) exclaiming that to be considered resilient and compassionate educators, EFL teachers should be able to balance their emotions, feelings, and stress accordingly to be more adaptable responding to various unpredictable teaching-learning events recurring in their classroom circumstances. In a like manner, Lacaba et al, (2020) LET: Linguistics, Literature and Language Teaching Journal Vol. 11 No.…”
Section: Miss Luna)mentioning
confidence: 99%
“…Again, to sustainably sustain EFL Nevertheless, teachers should be provided with ample and flexible opportunities to corroborate their resilience along with professionalism by asking them to deliberately select a bunch of teaching-learning activities suitable for their current learning contexts to promote holistic educational ventures wherein both teachers and learners are flourishing altogether. Lacaba et al, (2020) in their study of EFL teachers' resilience, commitment, and teaching effectiveness suggested educational institutions juxtaposing the equilibrium between internal and external supports imparted to EFL teachers to help them develop their professionalism along with resilience eventually resulted in the fulfillment of the desired teaching-learning objectives and outcomes. Specifically, there were five prior studies mutually associated with the major theme of this study.…”
Section: Introductionmentioning
confidence: 99%